AKTIVITAS PEMBELAJARAN KOOPERATIF JIGSAW DALAM MENINGKATKAN HASIL BELAJAR SISWA SMP PADA MATERI PERSAMAAN LINEAR DUA VARIABEL - Su'fatul Ulum (Universitas Sultan Ageng Tirtayasa, 2020)
This research is motivated by low student learning outcomes on Multivaribel linear equation topic. To overcome the problem, then used model cooperative learning type Jigsaw. The research subject is a grade VIII student of SMPN 13 Kota Serang. The instrument used is a test given on each cycle. Based on the results of data analysis, there is a significant increase in student learning outcomes after using the cooperative learning type Jigsaw model. It can be seen from the improvement of learning outcomes on each cycle. In cycle III also experienced increased ability to resolve the problem, proven from students who complete the classical learning by 85.70%. The average score students reached cycle III is 76.6. It’s mean there is an increase in the students' ability to solve the problem of linear equations with two variables. While observing the teaching and learning activities by other teachers, the teacher's activities have improved over cycle I and cycle II, which is the teacher's attention is complete to the students.Keywords: Cooperative Learning, Jigsaw, Learning Outcome